Dory Fantasmagory : Tiny Tough - Book 5 - Hanlon, Abby ([Place of publication not identified] : Dial Books)
"Dorys sure that her big sisters friendship troubles have to do with pirates, but shell have to navigate those rocky waters without her imaginary first mate Mary, whos found an exciting new pal of her own"--
Keywords: pirates; alone; Imaginary companions; Junior Fiction